Security Issues in the Use of Mobile Educational Apps: A Review - Mkpojiogu, Emmanuel O.C.; Hussain, Azham; Agbudu, Monday Onah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Although, there are several literatures pertaining to the security issues in the use of mobile apps, these literatures do not sufficiently address issues about the security challenges in the use of mobile educational app. Hence, this work attempts to review the available literatures with the aim of capturing the security issues in the use of mobile educational apps. To achieve the stated research goal, the study applied systematic literature review methodology. Sixty four (64) papers in the area of security issues in the use of mobile educational apps were downloaded. Out of these papers, twenty one (21) most relevant studies were selected for review in order to extract the appropriate information needed for the analysis. The results from the review reveals the scarcity of appropriate literatures on security issues in the use of mobile educational apps and that these issues are a thing of concern, and needed to be looked into in this ever growing world of technologies. However, most of the studies, taken single handedly reviewed lack of comprehensive framework to demonstrate the security challenges in the use of mobile educational apps. Thus, the results from this paper provide additional knowledge to the users of mobile apps as a whole; students in their usage of mobile educational apps and the research community on the current security challenges in the use of mobile educational apps.